Communicative Language Teaching - Norsubxonova Dilshoda Jamshid qizi (Periodica Journal, 2024)
Communicative language teaching (CLT), or the communicative approach (CA) , is an approach to language teaching that emphasizes interaction as both the means and the ultimate goal of study
Keywords: Communicative language teaching; communicative approach; classroom activities